2017
DOI: 10.1093/rheumatology/kew480
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative chest computed tomography is associated with two prediction models of mortality in interstitial lung disease related to systemic sclerosis

Abstract: QCT assessment of SSc-ILD can discriminate between well-defined different mortality risk categories, supporting its prognostic value. These findings, together with the operator independence, strengthen the validity and clinical usefulness of QCT for assessment of SSc-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Quantitative methods overcome the inter-observer grade of concordance, but are not able to distinguish the main feature of lung damage. Moreover, both semiquantitative and quantitative methods were associated with mortality and PFTs at baseline [25][26][27], but this correlation was not always confirmed in the follow-up. A possible explanation is that a reduction in the total amount of GGOs, with a consequent increase in the proportion of HC, could not change quantitative values, but it is associated with an impairment of PFTs.…”
Section: Discussionmentioning
confidence: 92%
“…Quantitative methods overcome the inter-observer grade of concordance, but are not able to distinguish the main feature of lung damage. Moreover, both semiquantitative and quantitative methods were associated with mortality and PFTs at baseline [25][26][27], but this correlation was not always confirmed in the follow-up. A possible explanation is that a reduction in the total amount of GGOs, with a consequent increase in the proportion of HC, could not change quantitative values, but it is associated with an impairment of PFTs.…”
Section: Discussionmentioning
confidence: 92%
“…HRCT may also be useful as a prognostic factor in the assessment of ILD severity and progression. Emerging evidences support the role of many quantification scores in the evaluation of prognosis and response to treatment in several CTDs [132][133][134].…”
Section: First-line Instrumental Examsmentioning
confidence: 94%
“…137 Several studies showed that QCT is an objective analysis that may overcome the issue of the interobserver variability and could provide more consistent prognostic indexes. [138][139][140][141][142] Furthermore, QCT has the potential ability to identify CT features that are not visually recognizable and to objectively monitor the disease progression on serial CT scans.…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…systemic sclerosis). 141,142,145,146,150,156,158 At present, automated image analysis of ILD is still confined to the research setting.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation